2021
DOI: 10.1101/2021.09.30.462689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress response inEntamoeba histolyticais associated with robust processing of tRNA to tRNA-halves

Abstract: tRNA-derived fragments have been reported in many different organisms and have diverse cellular roles such as regulating gene expression, inhibiting protein translation, silencing transposable elements and modulating cell proliferation. In particular tRNA halves, a class of tRNA fragments produced by the cleavage of tRNAs in the anti-codon loop, have been widely reported to accumulate under stress and regulate translation in cells. Here we report the presence of tRNA-derived fragments in Entamoeba with tRNA ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has also been shown that amoebic EVs contain tRNA halves and tRFs which associate with E. histolytica AGO proteins Eh AGO2-2 and Eh AGO2-3 [ 48 ]. Prior to EV collection, parasites were cultivated in serum-free medium to prevent contamination with bovine serum EVs.…”
Section: Trna-derived Small Rnas (Tsrnas) In Protozoan Parasitesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that amoebic EVs contain tRNA halves and tRFs which associate with E. histolytica AGO proteins Eh AGO2-2 and Eh AGO2-3 [ 48 ]. Prior to EV collection, parasites were cultivated in serum-free medium to prevent contamination with bovine serum EVs.…”
Section: Trna-derived Small Rnas (Tsrnas) In Protozoan Parasitesmentioning
confidence: 99%
“…Thus, serum starvation is a trigger that prompted increased production of tRNA halves which is common in other organisms where tRNA cleavage into halves is induced during nutritional and oxidative stress [ 17 , 70 , 71 , 72 , 73 ]. Most of the tRNA halves originated from a few tRNAs, particularly tRNA Ala (AGC), tRNA Ala (UGC), tRNA Arg (UCU), and tRNA Asp (GUC) [ 48 ]. The biogenesis of tsRNA can be highly affected by tRNA modifications [ 16 ].…”
Section: Trna-derived Small Rnas (Tsrnas) In Protozoan Parasitesmentioning
confidence: 99%
See 1 more Smart Citation